Toxic effects of a mixture of pharmaceuticals in Mytilus galloprovincialis: The case of 17α-ethinylestradiol and salicylic acid. (1st May 2023) - Cunha, Marta; Silva, Mónica G.; De Marchi, Lucia; Morgado, Rui G.; Esteves, Valdemar I.; Meucci, Valentina; Battaglia, Federica; Soares, Amadeu MVM.; Pretti, Carlo; Freitas, Rosa
Abstract: The impact of pharmaceuticals on marine invertebrates has been a topic of rising concern, with an increasing number of studies regarding the impacts on bivalves. However, very few investigated the toxicity of mixtures of pharmaceuticals. This knowledge gap was investigated in the present study, where the toxicity of 17α-ethinylestradiol (EE2) and salicylic acid (SA) mixture was evaluated. To this end, Mytilus galloprovincialis mussels were chronically subjected to both pharmaceuticals, acting alone and in combination, and the effects at the cellular level were measured. The Independent Action (IA) model was performed aiming to compare obtained with predicted responses. The integrated biomarker response (IBR) index was used to assess the overall biochemical response given by mussels. The results obtained revealed that the most stressful condition was caused by the combined effect of EE2 and SA, with the highest metabolic capacity, antioxidant (catalase activity) and biotransformation (carboxylesterases activity) activation and cellular damage in organisms exposed to the mixture of both drugs in comparison to responses observed when each drug was acting alone. Predicted responses obtained from the IA model indicate that caution should be paid as frequent deviations to observed responses were found. This study highlights the need for future studies considering the mixture of pollutants, mimicking the actual environmental conditions. Graphical abstract: Image 1 Highlights: Mytilus galloprovincialis metabolism was higher in the presence of the drug mixture. 17α-ethinylestradiol and Salicylic acid activated mussels' antioxidant capacity. Antioxidant and detoxification defenses were higher when both drugs were mixed. Cellular damage occurred when both drugs were acting in combination.